Investigating the potential for energy flexibility in an office building with a vertical BIPV and a PV roof system. (July 2019) - Aelenei, Daniel; Lopes, Rui Amaral; Aelenei, Laura; Gonçalves, Helder
Abstract: Building Integrated Photovoltaics (BIPV) are becoming an attractive solution in the context of high penetration of photovoltaics (PV) in buildings caused by the strive to achieve net or nearly zero energy status. Besides retrieving solar radiation to produce electricity, BIPV also offers aesthetical advantages because of its architectural feature. This paper reports on the electrical energy performance of a passive solar office building, Solar XXI, located in Lisbon, Portugal, which has installed on the South façade a BIPV (12 kWp) and an additional photovoltaic roof system in a nearby car park facility (12 kWp) for electricity generation. The main objective is to investigate the potential to increase load matching between energy generation and consumption and improve grid interaction for two scenarios using the energy flexibility enabled by the integration of Battery Energy Storage Systems (BESS) with capacities ranging from 13.5 kWh to 54 kWh. To collect the required results, real consumption and generation data are used, together with numerical simulations related to the integration of the BESS. The results show that load matching and grid interaction related metrics can be significantly improved by using the energy flexibility provided by a BESS and that the implementation of such system can be economically viable for a 10-year period.